Foreign Body Embedded in Anterior Chamber Angle - Shmuel Graffi; Beatrice Tiosano; Ran Ben Cnaan; Jonathan Bahir; Modi Naftali (Case Reports in Ophthalmological Medicine)
Introduction. We present a case of a metallic foreign body embedded in the anterior chamber angle. After standing in close proximity to a construction worker breaking a tile, a 26-year-old woman using soft contact lens for the correction of mild myopia presented to emergency department for evaluation of a foreign body sensation of her right eye. Methods and Results. Diagnosis was confirmed by gonioscopic examination and a noncontrast CT scan of head and orbits. The foreign body was removed by an external approach without utilizing a magnet. The patient's final outcome was favorable. Discussion. The above is a rare clinical situation, which is impossible to detect on slit-lamp examination without a gonioscopic view. Proper imaging and a specific management are mandatory in order to achieve favorable outcome.